Hellboy [videorecording (DVD)] - Beltrami, Marco (Columbia TriStar Home Entertainment, 2004)
In the 1940s, the Third Reich has joined forces with the evil Grigori Rasputin, who has used his occult powers to summon up a demon from the depths of Hell. However, the demonic creature is captured by American forces, and put in the care of Professor Broom. Under Broom's care, Hellboy develops the desire to do good. Sixty years later he takes action as part of an elite secret defense team alongside Liz Sherman, and Abe Sapian, an aquatic humanoid with the power of telepathy. Hellboy finds himself facing the powerful Rasputin determined to bring the demon back to the forces of darkness.